Diseño e implementación de un Sistema de Control en Red, utilizando sensores y actuadores inteligentes para los mecanismos de control: PID, PWM y Control on/off, monitoreados mediante una aplicación por la nube. - Bonilla Agualongo, Paúl Agustin (2016)
The various existing control systems exchange different types of data between field devices, the wide variety of networks and dedicated wiring to meet the requirements of the different levels of the automation pyramid have a high complexity configuration with high costs of acquisition and installation . In this project it proposes to design and implement a network control system, whose main characteristic is to use a shared medium that allows the controller to communicate with sensors and actuators in the field. A new proposal on control systems, with a protocol and general wiring that meets the needs of all levels of the automation pyramid, common information networks and industrial The proposal in this project network will monitor and display the various plant processes, multiple users can access data from control systems easily and quickly by the various devices within the network coverage.